2004
DOI: 10.1126/science.1096033
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbons in Hydrothermal Vent Fluids: The Role of Chromium-Bearing Catalysts

Abstract: Fischer-Tropsch type (FTT) synthesis has long been proposed to account for the existence of hydrocarbons in hydrothermal fluids. We show that iron- and chromium-bearing minerals catalyze the abiotic formation of hydrocarbons. In addition to production of methane (CH4aq), we report abiotic generation of ethane (C2H6aq) and propane (C3H8aq) by mineral-catalyzed hydrothermal reactions at 390 degrees C and 400 bars. Results suggest that the chromium component in ultramafic rocks could be an important factor for FT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
223
4
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(240 citation statements)
references
References 22 publications
7
223
4
2
Order By: Relevance
“…Chromite, Fe-Ni alloys, and magnetite have been shown to catalyze this reaction (Horita and Berndt, 1999;Foustoukos and Seyfried, 2004) and these and similar phases are abundant constituents of the CM chondrites (Brearley and Jones, 1998). At 200˚C (a temperature at which this reaction occurs over laboratory time scales), the CH 4 produced by this reaction is ca.…”
Section: Correlation Between δ 13 C Of the Carbonates And δ 18 O Of Tmentioning
confidence: 99%
“…Chromite, Fe-Ni alloys, and magnetite have been shown to catalyze this reaction (Horita and Berndt, 1999;Foustoukos and Seyfried, 2004) and these and similar phases are abundant constituents of the CM chondrites (Brearley and Jones, 1998). At 200˚C (a temperature at which this reaction occurs over laboratory time scales), the CH 4 produced by this reaction is ca.…”
Section: Correlation Between δ 13 C Of the Carbonates And δ 18 O Of Tmentioning
confidence: 99%
“…Thus, at least some role for inorganic methane seems inescapable unless net heating by water vapour and clouds was proportionally higher than currently assumed or a fourth factor is overlooked. Abiotic methane (Horita & Berndt 1999;Foustoukos & Seyfried 2004;Scott et al 2004a) is found, e.g. in deep mines in Canada and South Africa and in mid-oceanic rifts.…”
Section: Synthesis: How Microbial Quantum Evolution Changed the Worldmentioning
confidence: 99%
“…Chromite (FeCr 2 O 4 ), a primary mineral common in serpentinization systems, has been shown to enhance FTT synthesis reactions (17). Additionally, secondary minerals such as magnetite (Fe 3 O 4 ) and/or awaruite (Ni 3 Fe) are produced during olivine hydrolysis, providing increased opportunities for FTT catalysis (13,15,(18)(19)(20)(21).…”
mentioning
confidence: 99%